Measurements from conventional, digital and CT-derived cephalograms: a comparative study - Ghoneima Ahmed; Albarakati Sahar; Baysal Asli; Uysal Tancan; Kula Katherine (Sciendo, 2012)
Objective: The purpose of this retrospective radiographic study was to determine the reliability and reproducibility of skeletal and dental measurements of lateral cephalograms created from a computerised tomography (CT) scan compared with conventional and digital lateral cephalograms.